An optimized A-MSDU frame aggregation with subframe retransmission in IEEE 802.11n wireless networks - Saif, Anwar; Othman, Mohamed; K. Subramaniam, Shamala; Abdul Hamid, Nor Asilah Wati (Elsevier, 2012)
The IEEE 802.11n standard is defined to achieve a high throughput at the MAC layer. This high throughput is accomplished via many enhancements in both the physical and MAC layers. A key enhancement introduced in the 802.11n standard is frame aggregation. Two types of aggregation defined by the 802.11n standard, aggregate MAC service data unit (A-MSDU) and aggregate MAC protocol data unit (A-MPDU). Frame aggregation reduces both the headers and timing overheads at the MAC layer by aggregating multiple frames into a single large frame before being transmitted. The aggregation headers themselves still have a negative impact on the network performance especially when aggregating frames of small payload. Moreover, the lack of partial retransmission in the A-MSDU aggregation is behind its poor performance in error-prone channels. In this paper we proposed an optimized header A-MSDU frame aggregation (OHA-MSDU) with subframes retransmission capability at the MSDU level. The simulation results show the significance of the proposed scheme, especially for applications that have a small frame size such as VoIP.